Enhancing income through value-addition - Mishra, D S (Indian Horticulture, 2019)
The value-added products of underutilized fruits are rich source of fibre, vitamins, minerals, antioxidants and have therapeutic values. Many of them have medicinal values par excellence. Efforts were made at the station for development of value-added products like dried and dehydrated fruits, RTS, squash, candies, pickles and powders and condensed fruit juices through solar drying. Most of the products are stored for a year at ambient storage and chemical analysis of these products indicated that there is a decrease in vitamins and mineral composition throughout the storage period. However, they retain sufficient amount of vitamins and minerals to meet the daily requirement of healthy human body. Demand for underutilized fruit based products and profits could be increased through formation of smallself help groups and their training at station. However, still awareness on benefits of value addition and market promotion is required.